POTRET KARAKTERISTIK KEPEMIMPINAN PEREMPUAN (Analisis Semiotika Surat Al-Naml: 23-44) - Syafieh, Syafieh; Nurbaiti, Nurbaiti (Jurnal At-Tibyan: Jurnal Ilmu Alquran dan Tafsir, 2018)
This article discusses about the characteristic of woman leadership which described in the Alquran.  The Alquran specifically dokumenting a women who success leading her country in al-Naml. Moreover in the letter of the verse the are signs or symbols of interest that indicate the characteristic of leadership. Therefore, interest to research by using semiotic. Through a semiotic understanding, on surah An-Naml verse 23-44 not only describes the existence of woman leadership, but also describes the characteristics of  Balqis in leading the country of  Sabaâ. Some of the Balqisâs characteristic leadership are democrasy, wisdom, intelligent, diplomasy and she also loves peace. This story shows that phenomeno woman leadership there was in Alquran and she has good characteristics of woman leadership.